2020
DOI: 10.21203/rs.3.rs-20225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Total laparoscopic versus open pancreaticoduodenectomy for pancreatic ductal adenocarcinoma: a propensity score matching analysis with meta-analysis

Abstract: Background Pancreatic ductal adenocarcinoma (PDAC) is one of the leading causes of cancer mortality worldwide. Total laparoscopic pancreaticoduodenectomy (TLPD) have been used in the treatment of benign and low-grade diseases on the pancreatic head. It is necessary to expand the current knowledge on the feasibility and safety of TLPD for PDAC treatment. We aimed to assess the surgical and oncological outcomes of TLPD for patients with PDAC by comparing them with open pancreaticoduodenectomy (OPD). Methods Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Total laparoscopic surgery required longer operative time than open surgery, but less blood loss and blood transfusion. 19 Our study implied that left approach did not increase complications in LPD. Boggi et al found complication rates ranging from 18.1 -64.2%, with an average of 41.2%.…”
Section: Intraoperative and Postoperative Complicationsmentioning
confidence: 50%
See 1 more Smart Citation
“…Total laparoscopic surgery required longer operative time than open surgery, but less blood loss and blood transfusion. 19 Our study implied that left approach did not increase complications in LPD. Boggi et al found complication rates ranging from 18.1 -64.2%, with an average of 41.2%.…”
Section: Intraoperative and Postoperative Complicationsmentioning
confidence: 50%
“…Chen et al found that postoperative complications in the laparoscopic group were lower in both incidence and severity but not statistically signi cant. 19 None of our patients had DGE, bile leakage or bowel anastomosis leak.…”
Section: Intraoperative and Postoperative Complicationsmentioning
confidence: 69%